Analysis of Ecological and Economic Situation On The Border Territories Of The Prc And The Southern Zone Of The Russian Far East - STEPANKO, N.G. (The journal of contemporary issues in business and government, 2021)
In the modern world, cross-border (transboundary) regions acquire special significance for optimizing the economy of the country and its individual regions, as well as for realizing its national interests in the international space. Any economic activity is associated with the use of nature, with the emergence of new or the development of old production and natural relations, which inevitably generate a complex of problems and form the ecological state of the territory. Therefore, the study of the territorial structure of production, production and natural relations, their dynamics is important and relevant, and especially in the border areas, because these territories are affected by their own production and economic activities of adjacent territories. In this paper, we consider the border counties of Heilongjiang Province and the regions of the southern regions of the Far East. The material on the natural-resource potential of the studied territories, their economic activities was collected and analyzed. In addition, the characteristic of the ecological situation of the territories, as well as some calculated indicators (according to the necessary statistical information available), characterizing the ecological status and economic sufficiency of nature protection activity is given. The uneven economic development of the border territories of the regions of the Far East and Heilongjiang Province and, consequently, the unequal impact of the economic activities of the considered territories on the environment are revealed. It is obvious that there are many factors that determine the further effective cooperation. At the same time, it is pointed out the need for joint projects aimed at methodological development on the basis of a uniform reading of the rules of nature management and sanitary norms. It is also extremely important for cross-border territories, in addition to economic joint projects, to formulate and implement joint projects for the protection of the environment and rational use of natural resources.